Структурные типы английских терминологических единиц - Авезимбетова, А (SCIENCE and SOCIETY, 2016)
The article deals with the structural peculiarities of English terminological units. The object of the investigation is the structural types of scien- tific-technical terms. In the result of the morphological analysis there were defined the following ways of formation of the terms: lexico-semantic,
Keywords: terminology; a definite notion; terminological units; the problem under discussion; internationalisms; scientific-technical text; acro- nyms; shortened terms